THE USE OF BOGGLE GAME TO IMPROVE STUDENTS VOCABULARY IN WRITNG DESCRIPTIVE TEXT - Fauziah, Amanda; Apriliaswati, Rahayu; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractVocabulary problem is the common problem faced by many students in writing. The restricted vocabulary will affect the students’ English skill. The purpose of this research is to investigate the use of boggle game can improve the students’ vocabulary mastery in descriptive text to the VII C grade students’ of SMP Negeri 1 MempawahHilir in academic year 2015/2016. The method in this research is classroom action research. The research was conducted in three cycles. The subject of this research consisted of 28 students who belonged to VII C grade of SMP Negeri 1 MempawahHilir in academic year 2015/2016. In collecting the data, the writer used observation checklist and field notes. By conducting the classroom action research, it is found that the use of boggle game improved students’ vocabulary in spelling aspect by linking the letters. Boggle game also improved meaning aspect by translate and re-write. The improvement showed in every cycle. On the first cycle there were 32,2% of students who had passed KKM score. On the second cycle improved to 67,8%. On the third cycle improved to 92,9%. In conclusion, the student’ vocabulary in descriptive text had improved by using boggle game. In other words, boggle game can help the students in spelling and meaning aspect which help them in writing descriptive text.Keywords : Boggle game, Improve, Vocabulary, Descriptive Text